Analisis Keterpilihan Sabilillah Ardie Dalam Seleksi Calon Wakil Bupati Dari Partai PKB Pada Pemilihan Kepala Daerah (PILKADA) 2018 Di Kabupaten Tegal - AKHMAD ABDUL MUHYI; Sulistyowati . (Journal of Politic and Government Studies, 2020)
The change of formation that occurs in candidate pair number 3 in the 2018 regionalhead election in Tegal Regency is a form of necessity. This change of formation occurredafter the incumbent candidate Entus Susmono died 47 days before polling day. Thereplacement has been regulated in KPU regulation No. 3 of 2017 so that one of the effortsmade by the bearer party then is to recruit a replacement candidate with a maximum timelimit of 7x24 hours or 7 days from the death of one of the candidates. This is interesting tostudy because cases of permanent absence due to death are very rare, so it is necessary tolook at how the bearer party chooses to replace the candidate. The purpose of this study is toprovide recommendations in the form of political studies to political parties regarding localelections.This study uses a qualitative method. This method aims to explore and understand thesituation that occurs so as to get an answer and produce descriptive data accurately. Datacollection techniques used were interviews and document review. Informants in this studywere the Chairperson of the Tegal Regency DPC PKB, the Chairperson of the Tegal RegencyDPC PKB Shura Council, the Chairperson of the candidate pair winning team number 3, theelected Vice Regent Sabilillah Ardie, the Chairperson of the Tegal Regency KPU, and theChairperson of the Tegal Regency PCNU.The results of this study indicate that the election of Sabilillah Ardie as a candidatefor Vice Regent after the death of Entus Susmono was carried out by the bearer party bylooking at various considerations, including political considerations, economicconsiderations and social considerations. The recruitment process carried out by the bearerparty in this case the PKB party in selecting candidates for vice regent candidates is to use aclosed model through rational choice of these considerations.The recommendation given is in the form of advice to the supporting party, namelyPKB in the future is expected to be able to expand supporters from various elements ofsociety, bearing in mind that currently the strong supporters of the Tegal Regency PKB areconsidered to only come from Nahdiyin which is sheltered by the Tegal Regency PCNU, andthen the role of political parties in party cadre, it is expected to be able to produce the bestcadre members so that in the future the party will no longer find it difficult to find areplacement candidate if unable to keep up.Keywords: Substitution of Candidates for Deputy Regent, PKB, Election of Regional Head